Anti-bacterial and anti-inflammatory properties of Vernonia arborea accelerate the healing of infected wounds in adult Zebrafish - Lalitha Vaidyanathan; T. Sivaswamy Lokeswari (BMC, 2024)
Abstract Background Management of wounds and healing under impaired conditions are the major challenges faced globally by healthcare workers. Phytocompounds which are anti-microbial and capable of modulating inflammation contribute to overall wound healing and regain of the lost structure and function especially in wounds impaired with polymicrobial infection. Methods An acute cutaneous impaired wound model using adult zebrafish was validated to simulate mammalian wound pathophysiology. This model was used to evaluate phytofractions of Vernonia arborea in the present study, for reduction of infection; myeloperoxidase (MPO) as a marker of infection; neutrophil infiltration and resolution; kinetics of inflammatory cytokines; and wound repair kinetics (viz., nitrite levels and iNoS expression; reepithelisation). Results Four fractions which were active in-vitro against five selected wound microbes were shown to reduce ex-vivo microbial bioburden upto 96% in the infected wound tissue. The reduction in CFU correlated with the neutrophil kinetics and MPO enzyme levels in the treated, wound infected zebrafish. Expression of pro-inflammatory cytokines (IL-6 and TNF-α) was downregulated while upregulating anti-inflammatory cytokine (IL-10), and nitric oxide signalling with fourfold increase in iNOS expression. The adult zebrafish wound model could well serve as a standard tool for assessing phytoextracts such as V. arborea for wound healing with anti-microbial properties. Graphical Abstract